Lecturers Awareness and Integration of Learning Space Technology for Instructions in Nigeria - Odewumi, Michael Olubunmil (Unnes Science Education Journal, 2020)
Learning Space is imperative in content delivery in institutions of higher learning. However, despite its value and worth to instructional delivery, the awareness and integration to instruction in Nigeria University by the lecturers have not been significantly established. Therefore the objectives of this study were to examine the lecturers’ awareness of learning space and investigate the lecturers’ integration of learning space for instruction at the University of Ilorin, Nigeria. The study was of a descriptive nature and cross-sectional survey. 120 lecturers was sampled in the faculty of education, University of Ilorin, Nigeria. Stratified sampling procedure, was used to grouped lecturers along gender. The self designed questionnaire was administered to 120 lecturers of 60 males and 60 females. Mean scores was utilised to answer research questions. Research hypotheses were tested with t-test statistical analysis at 0.05 level of significance. The findings of the study were that lecturers had positive awareness and integration of learning space technology for instructions delivery at University of Ilorin Nigeria. The study further recommended that lecturers should be encouraged to have more knowledge of learning space for teaching and learning and they should be educated on how to use learning space for their various instructions.